Relationship Between Left Ventricular Ejection Fraction And Age With Major Cardiovascular Incidence In Nste-Acs Patients - Gionina Amelia Halim; Starry Homenta Rampengan; Edmond Leonard Jim (Riviera Publishing, 2025)
Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide, with non-ST-elevation acute coronary syndrome (NSTE-ACS) significantly contributing to morbidity and mortality. Left ventricular ejection fraction (LVEF) and age are critical factors influencing major adverse cardiovascular events (MACE). However, limited research has examined their combined impact on NSTE-ACS patients. This study aims to analyze the relationship between LVEF and age with the incidence of MACE in NSTE-ACS patients at Prof. Dr. R. D. Kandou General Hospital, Manado, from January to December 2023. A retrospective cohort study was conducted using medical record data from NSTE-ACS patients. The study examined LVEF, age, and MACE incidence over six months using Chi-Square and Fisher’s Exact tests. Among 85 patients meeting inclusion criteria, 42.35% experienced MACE. Patients with reduced LVEF had a significantly higher incidence of MACE than those with preserved LVEF. Older patients, particularly those in the 75–84 age group, exhibited a higher tendency for MACE. Statistical analysis confirmed a significant relationship between LVEF and MACE (p=0.006), while age showed a non-significant correlation (p>0.05). The findings highlight the importance of early LVEF assessment in NSTE-ACS patients to improve risk stratification and optimize management strategies. Future studies should explore interventions to mitigate age-related cardiovascular risks.